Pengaruh Model Pembelajaran Kooperatif Numbered Head Together (NHT) Terhadap Hasil Belajar Siswa - Latif Faqih Al-Qurroh (Gunung Djati Conference Series, 2022)
The purpose of this study to determine the improvement in student learning outcomes with the Numbered Head Together learning model. (NHT) on student learning outcomes in the Qur'an Hadith subject at MTs Persatuan Islam 40 Sarongge Sumedang. In this study using a quantitative approach with the Quasy Experiment method, the objects of research in this study were class VIII A, totaling 18 students and class VIII B, totaling 21 students at MTs Persatuan Islam 40 Sarongge, class VIII A as an experimental class with a learning model. Numbered Head Together (NHT) and class VIII B as the control class used a conventional learning model, namely the lecture method. Based on the results of hypothesis testing using the T-test, it was obtained that T-count > T-table was 3.11 > 2.03 with a significance level of 0.05. In addition, it can be seen from the posttest results that the experimental class using the Numbered Head Together (NHT) learning model has an average score of 80.6, much higher than the control class using the conventional learning model, which has an average score of 63.8. Then based on the calculation of N-gain the score is 61.62. So from this study it can be concluded that the Numbered Head Together (NHT) learning model has an effect on student learning outcomes in the Qur'an Hadith subjects.